The Mind pain and healing - Ducat, Vivian; Eisenhardt, Robert; Hutton, Richard (The Mind series, 1988)
What is the mind's role in healing the body and controlling painn In this episode, you'll discover how attitude affects patterns of disease and pain. In a hypnosis demonstration, patient learn that the brain is actually an interpreter of pain. A person under hypnosis associates painful sensory input. The painkilling mechanism of the body also respond to expectation and placebos, allowing the mind to make associations that could have a powerful effect on the healing process.